Monitoring of milk performance of Wallachian sheep grazed under traditional Carpathian management in Western Beskids location - Martin Ptáček; Michal Milerski; Tereza Michlová; Jaromír Ducháček; Vladimír Tančin; Michal Uhrinčať; Jitka Schmidová; Filipp Georgijevič Savvulidi; Luděk Stádník (Czech Journal of Animal Science, 2023)
This study aimed to determine the potential of Wallachian sheep in quantitative and qualitative indicators of milk production under extensive conditions of the Western Beskids mountains. Milk samples were collected from the group of 38 non-dairying sheep selected from the basic 120-head flock. Ewes were monitored during four control days (from 27th April, the average 42nd day of lactation to 4th August, the average 142nd day of lactation) to cover the whole lactation period. Ewes were investigated for their milk production and for milk quantity parameter. Milk quality indicators included percentage estimation of milk components (fat, protein, casein, lactose, dry matter), somatic cell count (103 cells/ml), vitamin A and E content (mg/kg), and K, Mg, Ca, Zn, Cu (mg/kg) content. Milk production ranged from 1 017.37 g (early stage of lactation) to 416.87 g (late stage of lactation period). The milk contained high fat (6.06-8.44%) and protein (4.68-5.68%) percentages, low somatic cell count and favourable distribution of minerals and vitamins. In general, results of this study indicate a possibility for low-productive traditional grazing system with extensive sheep breeds not only for cultivating the area but also for the purpose of high nutritional food with beneficial aspect on human health.